Deaths within 90 days from starting renal replacement therapy in the ERA-EDTA Registry between 1990 and 1992 - Tsakiris, Dimitrios; Jones, Elizabeth H. P.; Briggs, J. Douglas; Elinder, Carl-Gusta; Mehls, Otto; Mendel, Shalom; Piccoli, Giovanni; Rigden, Sue P. A.; dos Santos, Jose Pintos; Simpson, Keith; Vanrenterghem, Yves (Nephrology, dialysis, transplantation, 1999)
Abstract. Background. Patients who die within 90 days of commencing renal replacement therapy (RRT) may be recorded by some centres and not others, and hence da